2007
DOI: 10.1097/01.nor.0000284652.83462.7e
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Function and Recovery Following Hip Repair Surgery

Abstract: Balance and cognitive ability were the best predictors of functional ability 3 months following discharge from a rehabilitation setting. As to return to functional ability following discharge, balance, cognitive status, and prior functional ability were the best predictors. Men reported higher functional levels 3 months following discharge and were more likely to return to their presurgical functional level. DISCUSSION/RECOMMENDATIONS: The significant influence of balance and fatigue on functional ability high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 32 publications
1
31
1
1
Order By: Relevance
“…Intervening conditions and factors such as comorbid conditions (Godfrey & Townsend, 2008), age, and personal outlook have been found to affect management of chronic conditions and recovery (de Pablo et al, 2004;Fitzgerald et al, 2004;Folden & Tappen, 2007;Majewski et al, 2005;Stamm et al, 2008); however, the results of this study showed that comorbid conditions might be more important than age, and that although the pace and extent of recovery might vary, a factor recognized by Godfrey and Townsend (2008), the reclaiming, refocusing, and reestablishing processes of recovery appear to be the same. In line with other studies (Fitzgerald et al, 2004;Folden & Tappen, 2007;Heine et al, 2004;MacDonald et al, 2005;Wong et al, 1999), the importance of relationships, social support, and a positive attitude was identified (Maliski, Rivera, Connor, Lopez, & Litwin, 2008;Montin et al, 2002).…”
Section: Discussioncontrasting
confidence: 61%
“…Intervening conditions and factors such as comorbid conditions (Godfrey & Townsend, 2008), age, and personal outlook have been found to affect management of chronic conditions and recovery (de Pablo et al, 2004;Fitzgerald et al, 2004;Folden & Tappen, 2007;Majewski et al, 2005;Stamm et al, 2008); however, the results of this study showed that comorbid conditions might be more important than age, and that although the pace and extent of recovery might vary, a factor recognized by Godfrey and Townsend (2008), the reclaiming, refocusing, and reestablishing processes of recovery appear to be the same. In line with other studies (Fitzgerald et al, 2004;Folden & Tappen, 2007;Heine et al, 2004;MacDonald et al, 2005;Wong et al, 1999), the importance of relationships, social support, and a positive attitude was identified (Maliski, Rivera, Connor, Lopez, & Litwin, 2008;Montin et al, 2002).…”
Section: Discussioncontrasting
confidence: 61%
“…5). Ces exercices sont indiqués notamment dans les suites de fracture du col fémoral et d'arthroplastie de hanche qui ont un impact sur les stratégies d'équilibration sagittale des personnes très âgées et dont la prise en charge peut influencer le pronostic fonctionnel [14]. L'allongement du temps d'appui monopodal sera provoqué soit par des exercices d'enjambement d'obstacles (Fig.…”
Section: Membre Inférieurunclassified
“…Rehabilitation strategies for orthopaedic injury focus on a limited range of motion and an inability to weight bear on the involved limb (Brander and Stulberg, 2006;Edson, 2006;Heckmann et al, 2006). Also, research has shown that functional ability following rehabilitation of an orthopaedic injury is highly influenced by injury induced gait imbalances (Folden and Tappen, 2007). Although treadmill training with PBWS has not been widely adopted for the rehabilitation of many orthopaedic injuries, its use in the rehabilitation of total hip arthroplasty has been shown to restore symmetrical walking ability better than conventional physical therapy (Hesse et al, 2003).…”
Section: Introductionmentioning
confidence: 98%